2017
DOI: 10.1016/j.athoracsur.2017.01.055
|View full text |Cite
|
Sign up to set email alerts
|

The Paradoxical Relationship Between Donor Distance and Survival After Heart Transplantation

Abstract: Longer distances between donor location and center of heart transplantation are associated with a reduced hazard for survival at 30 days and 1 year, despite greater ischemic times. Future studies are necessary to elucidate the protective factors surrounding long-distance heart donation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 15 publications
1
10
0
1
Order By: Relevance
“…Despite long IT and travel distances, good outcomes can be achieved both in pediatric and adult recipients particularly using pediatric donors. 14,97,98 Donor preservation…”
Section: Electrocardiogram (Ecg)mentioning
confidence: 99%
“…Despite long IT and travel distances, good outcomes can be achieved both in pediatric and adult recipients particularly using pediatric donors. 14,97,98 Donor preservation…”
Section: Electrocardiogram (Ecg)mentioning
confidence: 99%
“…Further, while there is an obvious direct relationship between DIT and travel time, they are not identical and the correlation between the two is often poor. One large retrospective adult study of over 14 000 transplants demonstrated that when accounting for DIT, transplant center volume, and both recipient and donor characteristics, a 7% reduction in mortality at 30 days and a 6% reduction in mortality at 1 year were noted for every 100‐mile increase in donor‐recipient distance; there were no distance related‐survival differences in unadjusted Kaplan‐Meier curves . Conversely, the authors did find DIT to be an independent predictor for mortality at both 30 days and 1 year, and they hypothesized that after controlling for the detrimental impact of prolonged DIT, there must be a hidden, protective association between recipient survival and longer donor distances, which may be a surrogate for differences in myocardial cooling times or preservation practices.…”
Section: Donor Ischemia/travel Timementioning
confidence: 99%
“…Conversely, the authors did find DIT to be an independent predictor for mortality at both 30 days and 1 year, and they hypothesized that after controlling for the detrimental impact of prolonged DIT, there must be a hidden, protective association between recipient survival and longer donor distances, which may be a surrogate for differences in myocardial cooling times or preservation practices. Certainly from the existent data, despite long DIT and travel distances, good outcomes can be achieved in both pediatric and adult recipients …”
Section: Donor Ischemia/travel Timementioning
confidence: 99%
“…ОБЗОРЫ § В настоящее время большое количество научных работ посвящено непосредственным и отдаленным результатам ТС от доноров с расширенными критериями, такими как: возраст более 45-55 лет; наличие потенциально исправимой клапанной патологии донорского сердца; наличие поражения коронарных артерий; снижение систолической функции донорского сердца; несоответствие между весом донора и реципиента более 30 %; несоответствие по системе АВ0; наличие у донора СД, серопозитивного гепатита С, длительное время ишемии транпслантата, а так же использование донорского сердца с гипертрофией миокарда ЛЖ (ГЛЖ) более 1,4 см [22][23][24][25][26][27].…”
Section: трансплантация сердца от доноров с расширенными критериямиunclassified